2012
DOI: 10.1002/cmdc.201200337
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Telmisartan‐Derived PPARγ Agonists: Importance of Moiety Shift from Position 6 to 5 on Potency, Efficacy and Cofactor Recruitment

Abstract: Selective modulation of the peroxisome proliferator-activated receptor gamma (PPARγ) by direct binding of small molecules demonstrates a promising tool for treatment of insulin resistance and type 2 diabetes mellitus. Besides its blood pressure-lowering properties, the AT1-receptor blocker telmisartan has been shown to be a partial agonist of PPARγ with beneficial metabolic effects in vitro and in mice. In our previous work, comprehensive structure-activity relationship (SAR) studies discussed the different pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Partials agonists are defined as weak activators of PPARγ that elicit the same activation pattern as full agonists, but with a lower maximal activity. The antihypertensive agent Telmisartan is an angiotensin II receptor antagonist, but it has also been reported to function as a weak PPARγ agonist. , Scientists at GlaxoSmithKline optimized the telmisartan scaffold to afford GSK 7b, as a potent PPARγ partial agonist (Figure A) . A group at Amgen developed AMG-131 as a potent and highly selective PPARγ partial agonist that advanced into Phase 2 clinical trials .…”
mentioning
confidence: 99%
“…Partials agonists are defined as weak activators of PPARγ that elicit the same activation pattern as full agonists, but with a lower maximal activity. The antihypertensive agent Telmisartan is an angiotensin II receptor antagonist, but it has also been reported to function as a weak PPARγ agonist. , Scientists at GlaxoSmithKline optimized the telmisartan scaffold to afford GSK 7b, as a potent PPARγ partial agonist (Figure A) . A group at Amgen developed AMG-131 as a potent and highly selective PPARγ partial agonist that advanced into Phase 2 clinical trials .…”
mentioning
confidence: 99%
“…Through structure–activity relationship analysis of 72 , Matthias Goebel found that 1-(biphenyl-4-ylmethyl)-1 H -benzimidazole scaffold is an essential moiety (Figure ). The alkyl chains at C-2, such as ethyl or propyl, are appropriate for dual activities, while the methyl group at C-4 contributes to partial activity. , Substitution at C-5 is not conducive to ATI antagonism and PPARγ activation . The hydrophobic substitution at position 6 will help to enhance the activity of PPARγ without affecting the antagonism of ATI. , Yann Lamotte demonstrated that the replacement of the 1-methylbenzimidazole group in position 6 of 72 by an easily accessible carboxamide revealed a potent PPARγ partial agonist GSK7b. , …”
Section: Rational Design Of Multitargeted Ligandsmentioning
confidence: 99%
“…164,165 Substitution at C-5 is not conducive to ATI antagonism and PPARγ activation. 166 The hydrophobic substitution at position 6 will help to enhance the activity of PPARγ without affecting the antagonism of ATI. 164,167 Yann Lamotte demonstrated that the replacement of the 1methylbenzimidazole group in position 6 of 72 by an easily accessible carboxamide revealed a potent PPARγ partial agonist GSK7b.…”
Section: Rational Design Of Multitargeted Ligandsmentioning
confidence: 99%